Cutaneous Adverse Drug Reactions in Hospitalized HIV/AIDS Patients - Wibisono, Yusuf; Agusni, Indropo; Hidayati, Afif Nurul; Rahmadewi, Rahmadewi; Astindari, Astindari; Septiana, Septiana; Sari, Maylita; Murtiastutik, Dwi (Faculty of Medicine, Universitas Airlangga, 2021)
Background: Cutaneous adverse drug reaction (CADR) is the most common manifestation of drug hypersensitivity in humanimmunodeficiency virus (HIV), which presented as maculopapular rash. The incidence of CADR is found to be more commonin untreated HIV patients, and the frequency is higher in severe immunodeficiency status. Early diagnosis and appropriatetreatment give better outcomes. Purpose: To evaluate the incidence and management of CADR in HIV and acquired immunedeficiency syndrome (AIDS) patients. Methods: A retrospective descriptive study of HIV/AIDS patients with CADR whowere hospitalized at Intermediate Care and Infectious Disease Centre Dr. Soetomo General Academic Hospital. Result: Therewere more CADR cases in 2017, accounted 2.35% of the total Intermediate Care and Infectious Disease Centre RSUD Dr.Soetomo General Academic Teaching Hospital ward patients. There were more male patients (62.5%), with the mostcommonly found at the age of 25-44 years (64.3%), and which mostly (89.3%) originated from Surabaya. The most commondiagnosis was morbiliform eruption (60.7%), main complaint was red spots all over the body (45%), all of which are obscureerythematous macules. The most common causes were Duviral + Neviral antiretroviral (46%) and the most common treatmentwas dexamethasone injection. Conclusion: The incidence of CADR increased in 2017. The most frequent manifestation wasmorbilliform eruption due to Duviral+Neviral as the first line ARV treatment. Skin management varies widely in form oftopical, oral, and intravenous injection drugs, mostly using steroid class, dexamethasone intravenous injection in particular.